Use of controlled writing as an instrument for language proficiency in the paramedical professions - Salcedo, Julieta (Adsuara) 1944- ([Quezon City s.n.], 1973)
Proposal for the use of controlled writing for College Freshman English are presented in this paper. It provides graded writing techniques suited for the needs of students pursuing the paramedical professions. The instructional materials that this paper proposed are grouped under three units concerning the area of experience of the paramedical fields.
Thesis (M.A.T.English)--University of the Philippines.
Keywords: English language -- Composition and exercises; Medical writing